Analysis Glycol Losses On Gas Dehydration UnitPT X Field Z - Desi Kusrini, M.T. (Jurnal Bhara Petro Energi, 2023)
The dehydration process gas is a process of separation of gas from the water content by mixing an absorbent for example glycol, in PT X field Z process of dehydration of gas using triethylene glycol to decrease Water content Minimum below 7 lb / mmscfd to be sold to consumers. The goal of the research is to determine the water content that is absorbed in the contactor, knowing the number of glycol loss and knowing the cause of glycol loss after experiencing the process of dehydration. Every dehydrated process using glycol is always there whose name is glycol losses either in reboiler or contactor, but the losses are classified normal or abnormal loss, losses can be either liters or percentage loss glycol lost. To determine how much glycol is missing during the dehydration process then we have to look for production data such as gas flow rate data, inlet water content and outlet water content contactor then moisture content data, and the last data from glycol like SG Glycol and purity glycol, later from the data is known calculation of circulation glycol and know the amount of glycol loss whether the normal loss or abnormal loss. The water content omitted is 32.49 lbs / h while the Glycol losses found in the above-normal state are 0.35% with the lowest amount of Glycol losses of 0.02 gal / MMSCF and the largest 0.091 gal / MMSCF and the cause of Glycol loss Include the number of the tray, time, surface area of absorption, flow speed, and the temperature that is in the reboiler or the regeneration of glycol.